1994
DOI: 10.1103/physrevd.49.6039
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the role of instantons in hadron structure from lattice QCD

Abstract: Cooling is used as a filter on a set of gluon fields sampling the Wilson action to selectively remove essentially all fluctuations of the gluon field except for the instantons. The close agreement between quenched lattice QCD results with cooled and uncooled configurations for vacuum correlation functions of hadronic currents and for density-density correlation functions in hadronic bound states provides strong evidence for the dominant role of instantons in determining light hadron structure and quark propaga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
276
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(319 citation statements)
references
References 28 publications
41
276
2
Order By: Relevance
“…The latter case, usually referred to as the instanton liquid model (ILM) [5] (for a modern review see [6]), yields accurate estimates of vacuum condensates and hadronic correlation functions [7] for most light hadrons just by setting the mean distance between instantons to bē R ≈ 1 fm (which corresponds to a density N/V ∼ 1 fm −4 ) and the mean instanton sizeρ ≈ 1/3 fm. Lattice simulations have also supported the picture of a QCD vacuum dominated by instantons [8].…”
Section: A Instanton Liquid Models and Sχsbmentioning
confidence: 84%
“…The latter case, usually referred to as the instanton liquid model (ILM) [5] (for a modern review see [6]), yields accurate estimates of vacuum condensates and hadronic correlation functions [7] for most light hadrons just by setting the mean distance between instantons to bē R ≈ 1 fm (which corresponds to a density N/V ∼ 1 fm −4 ) and the mean instanton sizeρ ≈ 1/3 fm. Lattice simulations have also supported the picture of a QCD vacuum dominated by instantons [8].…”
Section: A Instanton Liquid Models and Sχsbmentioning
confidence: 84%
“…It was shown that instantons lead to spontaneous chiral symmetry breaking by introducing strong non-pertrubative correlations between fermionic zero-modes localized around the instanton positions. Specific features of the instanton picture have been observed in a number of lattice studies [5,6,7,8,9] and there is evidence that chiral symmetry breaking is correlated with smooth lumps of topological charge, whose profile is consistent with that of singular-gauge instantons [10,11]. In addition, instanton-induced correlations in hadrons have been studied in a number of phenomenological model calculations, where it was shown that the Instanton Liquid Model, (ILM), provides a good description of the mass and the electro-weak structure of pions, nucleons and hyperons [12,13,14,15,16,17,18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The estimates of these quantities are ρ ≃ 0.33 f m, R ≃ 1 fm, (phenomenological) [4], (2) ρ ≃ 0.35 f m, R ≃ 0.95 fm, (variational) [5], ρ ≃ 0.36 f m, R ≃ 0.89 fm, (lattice) [6,7,8,9,10] and have ∼ 10 − 15% uncertainty. Recent computer investigations [11] of a current mass dependence of QCD observables within instanton liquid model show that the best correspondence with lattice QCD data is obtained for ρ ≃ 0.32 f m, R ≃ 0.76 f m.…”
Section: Introductionmentioning
confidence: 99%